The Role of Values Education in Countering Violence - Gülerce, Hakan; Yapar, Osman Erdem (Journal of Islamic Thought and Civilization, 2020)
The problem of violence and its prevention is a central issue in the modern age. Acts of violence are often associated with the religious identities of the perpetrators. The misrepresentation of Islam and Muslims by the media and politicians has unfortunately become a common scenario. On the other hand, research into extremism, violence and terrorism proves that there are other factors than religion that prepare the fertile ground for such acts. Moreover, understanding the causes of violence and developing effective strategies to counter it as well as strengthening resilience in the community has become a significant need of governments, communities and individuals. This study adopted narrative literature review as its research method. The paper is organised in three main parts. The first part analyses theoretical and research based literature about the underlying factors that lead to violence. The second section focuses on values education as the means to develop resilience as well as resistance to violence with reference to relevant research studies. Intervention studies discussed in this section especially demonstrate practical applications of values education. The third section goes on to analyse a specific case in Turkish history in which values education was used to build resilience against persecution and violence. The principles of compassion towards others and wisdom in various areas of life are two main values found to be effectively used to counter violence. The authors suggest that the teaching and practice of these values can reduce violent acts towards others as well as build resilience against such acts when committed by others.